Sheath-assisted hydrodynamic particle focusing in higher Reynolds number flows - Panwar, Nishtha (2020)
Focusing of sample cells or particles to a single-particle stream in miniature flow cytometers is achieved using pressure-driven hydrodynamic focusing in microfluidic channels. Hydrodynamic focusing models predict the focused sample stream width in the low Reynolds number regime (Re 1) of the Navier-Stokes equations, wherein the viscous forces dominate the inertial forces. Nonetheless, operating in the viscous regime of the laminar microfluidic flow results in high relative focused stream width, and also limits the efficiency of microfluidic flow cytometers as sample throughput is low due to extremely low flow rates. Hence, to enhance the power of microfluidic cell focusing, study of the hydrodynamic focusing mechanism at high Re, and thus, the effect of inertial forces in sheath-assisted flows is required. This work presents a comparative analysis of sheath-assisted hydrodynamic particle focusing in both the viscous and inertial regimes. Experimental results for pressure-driven hydrodynamic focusing inside microchannels in the higher Re (60 < Re < 130) laminar regime are presented along with particle trajectory simulations. Furthermore, we present a comparison of the focusing performance of sheath-assisted hydrodynamic focusing at lower and higher Re. These studies underline the conditions for single-particle focusing for a range of flow parameters and relative particle sizes, particularly for microfluidic flow cytometry. Such analyses constitute an essential aspect of engineering miniature flow cytometers or other cell manipulation techniques.